Chemical composition and biomethane production potential of Euglena gracilis biomass and extraction residue from supercritical CO2 extraction. (September 2022) - Tossavainen, Marika; Edelmann, Minnamari; Lahti-Leikas, Katariina; Kivimäki, Satu; Kymäläinen, Maritta; Piironen, Vieno; Lampi, Anna-Maija; Ojala, Anne; Romantschuk, Martin
Abstract: The compositions of Euglena gracilis extracts and extraction residues from pilot scale supercritical CO2 extraction (SFE-CO2 ) were investigated using two extraction temperatures (30 and 50 °C). For comparison, lipids from initial biomass and from SFE-CO2 residues were extracted with accelerated solvent extraction (ASE). Fatty acid and tocopherol contents of all extracts, and protein and amino acid contents and biogas production potential of initial biomass and SFE-CO2 residues, were analyzed. Saturated fatty acids and tocopherols were extracted efficiently with SFE-CO2, whereas most of the polyunsaturated fatty acids remained in the extraction residue. Protein and amino acid contents in the initial biomass and SFE-CO2 residues were comparable. Biomethane production potential of the extracted biomass was slightly lower than that of the initial biomass, which was accounted for by the amount of extracted fatty acids. Proteins, amino acids and polyunsaturated fatty acids were not degraded in SFE-CO2, indicating that they could be further utilized. Graphical abstract: Unlabelled Image Highlights: Saturated fatty acids and tocopherols are efficiently extracted with SFE. Amino acids and polyunsaturated fatty acids are not degraded in SFE. Biogas production potential of de-fatted E. gracilis biomass is high.